A bibliometric analysis of the evolution and impact of reference services and information literacy programs in academic libraries (2014-2024) - Yusof, Siti Khairiah; Sulaiman, Mohd Abdul Halim (Faculty of Information Management, 2025)
This study presents the bibliometric analysis on topic of Information Literacy (IL) program and reference services in academic libraries. The main objective of this study is to examine the correlations between 3182 research papers cited from the year 2014 to 2024 in Scopus-indexed scholarly publications. This study means to systematically analyse the topic research trends, identify authors, influential journals and emerging topics to provide insights into the evolution and impact of the academic libraries IL and reference services. This study answered the two research questions with the significant results that contribute to research growth. From the findings, it has been a substantial increase in the number of articles in peer-reviewed journals over the years and provides insights of academic libraries evolved to meet the demands of the rapidly changing information and technology landscape and will shapes the future optimization of academic libraries service.